Ramadan Fasting in Relation to Salivary Uric Acid and Selective Physical Parameters - Abdul Kareem Hussein, Ryam; Hussein Awn, Baydaa (Diyala Journal of Medicine, 2024)
Background: Ramadan is the holy month in which all Muslims abstain from eating and drinking from sunrise to sunset. The impact of Ramadan fasting on the oral cavity and saliva needs more attention because of the important function of saliva in the protection of the mouth. Objective: To determine the impact of Ramadan fasting on salivary uric acid, flow rate, and pH among Iraqi male dental students. Patients and Methods: The subject population consisted of thirty healthy male dental students (College of Dentistry/University of Baghdad) with an age range of 20–23 years who intended to fast the whole of Ramadan (1443 Hijri calendar). Saliva samples were obtained from all dental students one week prior to the start of Ramadan, the last week of Ramadan, and one month after the end of Ramadan. The salivary flow rate was calculated, and the salivary pH was measured using a digital pH meter. Then a saliva sample was analyzed to detect the concentration of uric acid by using the spectrophotometer. Results: The data analysis for this study revealed that the salivary flow rate decreased from baseline to Ramadan and then increased again after one month of Ramadan with significant differences (p<0.05). While salivary uric acid increased continuously with significant differences from baseline to Ramadan and after one month of Ramadan fasting (p<0.05), on the other hand, salivary pH showed no significant differences (p > 0.05) among the three time periods of the study. Conclusion: Saliva was affected by Ramadan fasting through a decrease in salivary flow rate during fasting and a return to normal salivary flow rate after the end of Ramadan. In addition, uric acid, which acts as a salivary antioxidant, shows an increase during Ramadan fasting. Keywords: Ramadan fasting, salivary flow rate, salivary pH, uric acid